Anti-oxidative effects of catechins and theaflavins on glutamate-induced HT22 cell damage. Issue 37 (10th July 2019) - He, Jinting; Xu, Lei; Yang, Le; Sun, Caixia
Abstract : EGCG and TF3 attenuate glutamate-induced ROS production and cell apoptosis. Abstract : Background : Glutamate is an excitatory neurotransmitter that is involved in cell stress caused by oxidation. Polyphenolic compounds display various potential neuroprotective properties due to their ability to donate electrons and hydrogen atoms. Method : In this study, we evaluate the protective effect towards glutamate-induced HT22 cell damage. Two families of polyphenolic compounds are investigated, including the monomer polyphenol catechins, as well as the dimerized theaflavins. The cell apoptosis and intercellular ROS production are quantified by flow cytometry, and the protective mechanism is evaluated by quantifying the expression of cell apoptosis and energy related proteins. Result : Both sets of compounds protect cells against glutamate-induced oxidative stress, partially restore the cell viability, and prevent cells from apoptosis via bcl-2 and bax regulation, and attenuate intercellular ROS production. We demonstrate here that the protective effect is mediated by multiple factors, including reducing intracellular Ca 2+ concentration, increasing glutathione level and related enzyme activity. Thus, the phosphorylation of AMP-activated protein kinase (AMPK) and extracellular signal-regulated kinase (ERK) show inverse correlation of activity after catechins and theaflavins stimulation. Conclusion : These results suggest both catechins and theaflavins compounds protect cells from glutamate-induced damage via cell apoptosis-related proteins and indirect regulation of cellular energy enzymes. These natural sourced antioxidants provide potential therapeutic agents for glutamate accumulation and toxicity related diseases.